HCI in Southeast Asia: The journey forward - Sari, E. (Institutional Knowledge at Singapore Management University, 2022)
SEACHI 2022 has been conducted to bring HCI and UX leaders in Southeast Asia to discuss the current state-of-the-art HCI and UX teaching, practice, and support they experience in their region. This activity aims to explore the potentials and challenges and identify the gaps amongst different sectors in different countries. Through this workshop, we will have a common understanding of what we face. It explores how we can work collaboratively to achieve a better purpose, i.e., to grow HCI and UX fields in Southeast Asia. This one-day online workshop was conducted as a collocated event of CHI 2022 and was attended by delegates from Indonesia, Malaysia, Singapore, Thailand, and the Philippines. This paper is a summary of the individual papers produced by delegates.